Multi-variable model reduction of smart structure in active vibration control. Issue 25 (2018) - Wang, Peng; Scorletti, Gerard; Korniienko, Anton; Collet, Manuel
Abstract: In this paper, a new model reduction method is proposed to further reduce the structural model obtained by classical model reduction techniques. The reduction is in the frequency domain and is able to obtain a reduce-order model that is close to the initial model in a specified frequency range. The reduced-order model keeps the poles of the initial model in the frequency range of interest. Linear Matrix Inequality (LMI) is used to minimize the relative error. This method is effective on both single-input single-output (SISO) system and multi-input multi-output (MIMO) system. The application on a beam-piezo model with multiple actuators and sensors validates its effectiveness.